Beyond Bounds - Combrinck, Lisa (Department of English Language and Literature, 2024)
Like a slug, leaving a trail of mucus behind, I leave this long secretion of words. Stained pages, soiled underwear, spilled dreams. Life is not beautiful. It is the accumulation of scars, the imposition of cuts, the kniving of the womb, the stabbing of the soul, and the mind learning to lie and to live with the lies of its own making. Somewhere in this struggle, there appear glimpses of consummated desire, but they remain tiny, miniscule chinks oflight viewed from the bottom of the prison cell. Break open the bars. Walk in my womb. Bathe yourself in the presence of these words, the soapsuds of now. The lather of this page. But do not grow drunk. Do not water the future with these words. These words are too acidic, too acerbic, too alcoholic. They will burn and scar the future, rip and strip the body of its skin. Rather wipe out the residue that remains around this bowl. Douse the lava. Pull out the plug on these words. Let them seep down to the bottom of the drain. Let only echoes remain of the words whispering, gurgling into the underworld. Black-out everything. The dregs of my cup must not remain. No future must carve its route from these words. Every utterance must have its deathbed. And the dying must be able to choose whether their last words should be forgotten and die with them or whether they should be remembered and abused. I choose the former, euthanasia for the author, and plead with the reader not to be an informer, not to use these words for future seductions, mindless mutations of life. Now drive carefully. You have been forewarned. This is a cul-de-sac. Any attempts to press forward will be made in vain. Do not jump over the precipice of reality. You will find yourself back in the black hole of my womb. Frozen in time. Spiralling towards your end. In infinite cycles of erection and ejaculation. Pleasure which suddenly sours. The unending pain of permanent orgasm. Without pauses. Without breathing spaces. You do not have the stamina for this journey. Let me not whet your appetite for this kind of death. Do not lose your wits. Turn your back on this book. Go now. Before its brutal teeth make their presence felt. Run now. Every word is beyond repair. A song gone wrong. Every word is simply a swipe at your freedom, a fatal bite that sharpens your skin to the permanent perversions inherent in words. While I persist in playing pussy and pissing on the future. While I stroke your skin and suck the gaping hole in your soul. Escape now when you have the chance. Pull your naked self from under the covers of this book. Dress yourself in your own dreams, tmtouched by my hands. Forget the magnetic pull on your body parts, the throbbing longing in your loins. Walk away from this whoring of words, this story that is diseased in its spine. In the decalcifying of its bones. The petrifying of desire. The putrefying of privacy. This story that gets a kick out of selling itself, out of ripping its own knickers. This story that lingers interminably like stretch marks. Leave now. Wean yourself off these words. Weave your own song and go with the flow. Cleanse the world with your warm words. Let the future find its own form from your stream.